-7x+9x-4=6

Simple and best practice solution for -7x+9x-4=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x+9x-4=6 equation:



-7x+9x-4=6
We move all terms to the left:
-7x+9x-4-(6)=0
We add all the numbers together, and all the variables
2x-10=0
We move all terms containing x to the left, all other terms to the right
2x=10
x=10/2
x=5

See similar equations:

| 44=-9y+3y+2 | | x-3+x=13+6x | | (x/5)+2=5 | | -4(6x+1)=-40-6x | | 0.7y+2.5=0.95y-9.25 | | -483=7(-5+8v) | | -3(a-2)-2a=-14 | | 31=4x-8x-1 | | 7m-17=-3 | | 295=-5(5+8x) | | 5-4x-3+8=1 | | 3+-2=3x+(-2x)+5+(-2) | | -2+3(1+4x)=-19-8x | | -13=-(-3x-1)+5x | | 0.05x+0.04(12000-x)=560 | | 7(k-9)=77 | | 43​(x+8)=9 | | -4x+9=-3-6x | | -6x=3(x+9) | | 4+a/15=3 | | n+5(n+2)=20 | | 6x+9=-1+7x | | 5=1/3(t-6) | | 9b-2b=-14+9b | | 5-2*14}^{3.2x}=4 | | V=x(14-2x)(8.5-2x)(x) | | 3(-7x-8)=24+3x | | -4x-1+6=-7 | | 5×x=30-10 | | 5(x+4)=-6+5(x-2) | | 45n=580 | | Y=5/5u+5;u |

Equations solver categories